Halal Certificate Implementation and Purchasing Power of Muslim Teenagers - Ariyadi, Ariyadi; Norhani; A'ini, Nova Nur (CV. Ulil Albab Corp, 2025)
Halal certification plays an important role in the purchasing decisions of muslim youth, who are increasingly aware of the importance of halalness in the products they consume. This study aims to analyze how halal certificates affect product attractiveness and trust of muslim consumers. The method used is a qualitative approach with the type of phenomenology, this research collects data through observation, interviews, and documentation. The results showed that the existence of halal certificates provides a sense of security, increases loyalty, and contributes to product competitiveness in domestic and international markets. In addition, in the digital and e-commerce era, halal labeling is increasingly relevant in building consumer trust. Therefore, halal certification not only has religious value, but also serves as an effective marketing strategy for manufacturers.